2001
DOI: 10.1002/path.914
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction by sennoside laxatives in man; escape from a protective mechanism during chronic sennoside use?

Abstract: Chronic sennoside use induces melanosis coli (MC) and possibly increases colorectal cancer risk. Sennosides alter colonic crypt length, proliferative activity, and bcl-2 expression 18 h after administration. To investigate possible mechanisms for carcinogenesis, the effects of acute sennoside use and the presence of MC on colorectal epithelium were studied. Colorectal biopsies from 15 subjects receiving sennosides 6 h before sigmoidoscopy (Sen), 15 controls (NSen), and 27 with MC [11 moderate (MMC) and 16 seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…However, recent data, including those from large-scale retrospective, prospective and experimental studies, did not show any increased cancer risk. It is widely accepted that increase in the incidence of adenomas is probably due to easier detection of small adenomas against the black background [2,[19][20][21]. We had only one patient with adenoma and did not see any MC in proximal segments of patients with colon cancer.…”
Section: Discussionmentioning
confidence: 89%
“…However, recent data, including those from large-scale retrospective, prospective and experimental studies, did not show any increased cancer risk. It is widely accepted that increase in the incidence of adenomas is probably due to easier detection of small adenomas against the black background [2,[19][20][21]. We had only one patient with adenoma and did not see any MC in proximal segments of patients with colon cancer.…”
Section: Discussionmentioning
confidence: 89%
“…As has already been indicated, the chronic use of sennoside laxatives on some occasions causes pseudomelanosis coli [40] and this has been associated to an increase in the risk of colorectal cancer [41]. In patients subjected to enemas containing senna extracts, it was observed that the sennosides induce an acute massive loss of intestinal cells, possibly because of apoptosis, and alter the length of the colonic crypts causing the appearance of shorter crypts and an increase of the cellular proliferation and inhibition of the restoring apoptosis of the cellular function.…”
Section: Melanosis Coli and Apoptosismentioning
confidence: 99%
“…In conditions where severe melanosis coli was observed, apoptosis seems to be delayed, causing longer crypts without an increase of the proliferating activity or the expression of bcl-2, antiapoptotic gene. It has been suggested that the loss of a possible protective mechanism may increase the risk of carcinogenesis during the chronic use of sennosides [41]. …”
Section: Melanosis Coli and Apoptosismentioning
confidence: 99%
“…Anthranoid laxatives have been shown to induce apoptosis of colonic epithelial cells in man within 6 h after ingestion (Van Gorkom et al, 2001). Animal studies also demonstrated increased apoptosis 6 h after danthron administration (Walker et al, 1988).…”
Section: Discussionmentioning
confidence: 99%